Penerapan Flash Card sebagai Bahan Ajar Berbasis PBL untuk Meningkatkan Pemahaman Materi Mengenal Perasaan Murid Kelas II SD - Ramadhanti, Dara Ayu Alisa; Purwati, Panca Dewi (YASIN, 2025)
Although visual instructional media have been widely discussed in previous research, studies that specifically integrate flash cards with a Problem-Based Learning model to enhance understanding of “recognizing emotions” among lower-grade pupils remain limited. This study aims to analyze the effectiveness of implementing Problem-Based Learning-based flash cards in improving pupils’ understanding of various types of feelings in Bahasa Indonesia learning. A mixed-methods approach with an explanatory sequential design was employed, involving 28 second-grade pupils selected through purposive sampling. Data were collected through pretest–posttest assessments, classroom observations, and interviews, and were analyzed using descriptive statistics, N-gain analysis, and qualitative analysis based on the Miles and Huberman model. The findings show that learning using Problem-Based Learning-based flash cards significantly improves pupils’ understanding, as evidenced by an increase in the average score from 65 to 83 and an N-gain value of 0.56 in the medium category. These results reinforce the relevance of constructivist theory and demonstrate that visual representations linked to authentic problem solving can enrich pupils’ emotional understanding. The study underscores the importance of using contextual visual teaching materials in Bahasa Indonesia instruction and recommends further research with a broader range of schools using quasi-experimental designs and exploring other forms of visual media.